Safety profile of MenB-FHBp vaccine among adolescents: data from surveillance of Adverse Events Following Immunization in Puglia (Italy), 2018–2020. Issue 1 (31st December 2022) - Stefanizzi, Pasquale; Bianchi, Francesco Paolo; Martinelli, Andrea; Di Lorenzo, Antonio; De Petro, Paola; Graziano, Giusi; Lattanzio, Sabrina; Diella, Giusy; Stella, Paolo; Ancona, Domenica; Tafuri, Silvio
ABSTRACT: MenB-FHBp was licensed in Europe in 2017 from the age of 10. In the "postmarketing life" of a new vaccine, surveillance of Adverse Events Following Immunization (AEFI) is crucial, to better understand the pattern of safety and the effectiveness. This paper describes the MenB-FHBp AEFIs notified in Puglia in 2018–2021, to take a picture of the safety profile of this vaccine in the real life, four years after its introduction in Italy. This is a retrospective observational study. Data were collected from the list of AEFIs notified after MenB-FHBp vaccine administration in Puglia in 2018–2020, and the number of doses of this vaccine administered in the same period. AEFIs were classified according to WHOʻs algorithm, and causality assessment was carried out for serious AEFIs. From January 2018 to December 2020, in Puglia, 43, 061 doses of MenB-FHBp were administered and 42 MenB-FHBp AEFIs (reporting rate: 97.5 per 100, 000 doses administered) were reported. Among these, 12 were classified as severe (28.6%; reporting rate 27.9 per 100, 000 doses). Overall, the male/female ratio in AEFIs was 1:1. The median age of people who suffered from AEFIs was 12 years (range 11–13). For the 11 serious AEFIs for which the classification was "consistent causal association, " the diagnosis was hyperpyrexia (reporting rate 13.9 per 100, 000 doses), fainting (rate 4.6 per 100, 000 doses), urticaria (rate 2, 3 per 100, 000 doses), convulsions (rate 2, 3 per 100, 000 doses), and vomit (rate 2, 3 per 100, 000 doses). No deaths or impairment were notified in studied AEFIs. The picture of MenB-FHBp vaccine supports that the risk of AEFIs is in line with previous published data and in general acceptable.